Does Organizational Justice Modify the Association Between Job Involvement and Retirement Intentions of Nurses in Finland?. Issue 5 (27th June 2016) - Sulander, Juhani; Sinervo, Timo; Elovainio, Marko; Heponiemi, Tarja; Helkama, Klaus; Aalto, Anna‐Mari
Abstract: Given the growing aging population in Finland, retaining health staff to care for them is important. In an exploration of predictors of quitting before the typical retirement age, which ranges from 63 to 68 years in Finland, we examined whether organizational justice moderated the association between job involvement and retirement intentions among nurses 50 years and over. The sample was 446 nurses (70% practical nurses) working in 134 assisted living facilities providing 24‐hour care for older residents in Finland. Job involvement was measured with the Job Involvement Questionnaire, and organizational justice with a scale that tapped its three dimensions: distributive justice, procedural justice, and interactional justice. In covariance analyses, low organizational justice and low job involvement were associated with a higher likelihood of retirement intention. Both interactional justice and procedural justice moderated the association of job involvement with retirement intentions. Among nurses with low job involvement, those who experienced unjust treatment, that is, low interactional justice, and evaluated organizational procedures as unjust had significantly stronger retirement intentions than nurses with high levels of interactional and procedural justice. Distributive justice was associated with retirement intentions in both high and low job‐involved respondents. Organizational justice may act as a buffer against retirement intention as one consequence of nurses' low job involvement. © 2016 Wiley Periodicals, Inc.